Arbitary Pole-Placement in the LQ Control Paradigm - Keviczky, L.; Bokor, J. (Acta Technica Jaurinensis, 2013)
The specific relationships between the classical pole-placement state feedback, the Riccati equation based LQ paradigm and the Kalman frequency domain approach are discussed. It is shown that arbitrary pole placement is not possible by standard LQ optimality. A possible solution of this anomaly is to use more general LQ criterion with specific weights on the state, input and crossterm.